Origami toolkit: metaheuristic framework for combinatorial optimization problems: a machine learning tool for problem-solving and decision-making - Peres, Fernando Augusto Junqueira (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics